Computational analysis of nanofluids in heat exchanger - Chan, Shi Wei (2014)
In this paper is to study the performance of heat exchangers by using computational analysis method. In past decade years, many researchers had discovered that nanofluids have a brilliant efficient in the heat transfer process. They believes that applied the nanofluids in the heat transfer equipment would brings a better enhancement compare with the conventional cooling fluids. In the literature journals, the authors have specified focused on the thermal conductivity specific, heat, density, and viscosity of nanofluids. They believe these are the most significant factors of the working fluids that would influence the efficiency of heat exchanger. In this study, an imitated real-life marine transport used of shell and tube heat exchanger to be analyzed. The shell and tube sides of heat exchanger will be filled with Water or nanofluids and Water or SeaWater in respectively. The nanofluids will be assumed as single-phase nanofluids with variant of volume fraction of copper and alumina. The computational result of Water at the shell and tube sides will be used as validation of data compared with the technical performance specification given by the supplier. Further, the efficiency of different volume fraction of nanofluids and the optimum of volume fraction of nanofluids in this system would be discussed in the simulation results.